Navigating Financial Performance & Firm Value in State-Owned Entreprices: The Moderating Role of Dividend Payouts During Uncertainty Period - Soejono, Fransiska; Sulastri, Sulastri (Journal of International Conference Proceedings, 2024)
This study aims to examine and analyze the effect of firm performance (ROE) and firm characteristics (Size) on firm value (PBV). The study involves two control variables: situation and industry type. Additionally, this research uses the DPR variable as a moderator for the relationship between ROE and PBV, as well as for the relationship between Size and PBV. This study includes 21 state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange, with a total of 345 firm-year observations. The findings of this study show that the ROE and Size variables have a negative and significant effect on PBV. Meanwhile, the DPR variable positively moderates the relationship between ROE and PBV, as well as between Size and PBV. The situation and industry type variables were found to have no effect on PBV. The implications are that companies need to be cautious in relying on ROE or large size as indicators to increase PBV. An appropriate dividend policy can be an important strategy to enhance or maintain firm value, particularly for large companies facing challenges in sustaining PBV. Companies need to balance dividend policies with investments for growth and manage organizational complexity to improve PBV.